Board structure, political influence and firm performance - An empirical study on publicly listed firms in China - HAN, Dongping (Institutional Knowledge at Singapore Management University, 2004)
The board of directors is the cornerstone of any effective corporate governance system. A well-structured board can effectively monitor and motivate management of a company for the benefit of the company's shareholders. This paper investigates the relationship between board structure and firm performance using a sample of 490 publicly listed firms in China. The characteristics of board structure we examined include: board size, inside/outside/independent directors, CEO/Chair duality, stock holdings of directors, the rewards to directors and aged directors. We find significant relationship between firm performance and three characteristics: the rewards to director, the stock holdings of directors and the existence of independent directors. We also find political influences on the effectiveness of boards. When state ownership is more than 50% (state-dominating), rewards and stock holdings of directors are useful. When state ownership is less than 50% (non-state-dominating), the existence of independent directors takes effects. In addition, our analyses indicate that state ownership affects firm performance. State ownership is positively related to firm performance in state-dominating group while negatively related to firm performance in non-state-ownership group.